Psyket i strålkastarljuset: Psykiatri och psykisk ohälsa i tre samtida svenska teaterföreställningar - Pettersson, Cecilia (Passage - Tidsskrift for litteratur og kritik, 2025)
The Psyche in the Spotlight: Psychiatry and Mental Illness in Three Contemporary Theater Performances This article examines how the contemporary narrative of psychiatry and mental illness is adapted in three Swedish theater productions. The focus is on what Linda Hutcheon calls cultural adaptation. In summary, the performances portray a critical image of psychiatry, characterized by staff shortages and abuse of power. On the other hand, they nuance stereotypical perceptions of mental illness and problematize a division into sick and healthy.